Fluoride-mediated dephosphonylation of α-diazo-β-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkanna Babu; Wakchaure, Vivek Chandrakant; Ramana, Chepuri V. (Organic Letters, 2016)
The possibility of fluoride-mediated selective dephosphonylation of α-diazo-β-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting α-diazocarbonyl intermediates undergo a (3 + 2)-cycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess α-diazo-β-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.

Polymerizable solvent-free organic liquids: a new approach for large area flexible and foldable luminescent films - Wakchaure, Vivek Chandrakant; Veer, Sairam Dnyaneshwar; Nidhankar, Aakash D.; Kumar, Viksit; Narayanan, Aswini; Babu, Sukumaran Santhosh (Angewandte chemie-international editon, 2023)
The high demand for light-emitting and display devices made luminescent organic materials as attractive candidates. Solvent-free organic liquids are one of the promising emitters among them due to the salient features. However, the inherent limitations of forming sticky and noncurable surfaces must be addressed to become an alternate emitter for large-area device applications. Herein, we functionalized solvent-free organic liquids having monomeric emission in bulk with polymerizable groups to improve the processability. The polymerizable group on carbazole, naphthalene monoimide, and diketopyrrolopyrrole-based solvent-free liquid emitters enabled on-surface polymerization. These emitters alone and in combinations can be directly coated on a glass substrate without the help of solvents. Subsequent photo or thermal polymerization leads to stable, non-sticky, flexible, foldable, and free-standing large-area films with reasonably high quantum yield. Our demonstration of the tunable and white light-emitting films using polymerizable solvent-free liquids might be a potential candidate in flexible/foldable/stretchable electronics. The new concept of polymerizable liquid can be extended to other functional features suitable for futuristic applications.
Keywords: Energy Transfer; polymerization; Solvent-Free Organic Liquids; Thin-Film; White Light

Solvent-free organic liquids: an efficient fluid matrix for unexplored functional hybrid materials - Wakchaure, Vivek Chandrakant; Channareddy, Goudappagouda; Babu, Sukumaran Santhosh (Accounts of Chemical Research, 2024)
The invention of solvent-free organic liquids (SOLs) was serendipitous. However, the curiosity-driven research in the later stage delivered new soft materials with exciting optical, and optoelectronic properties along with appealing physical characteristics suitable for the futuristic applications. A slight change in the molecular design resulted in a drastic change in the physical state of molecules demonstrating monomer-like features in the bulk. The basic idea of core isolation has been successful in delivering new SOLs with attractive functional properties. The unique fluid matrix associated with SOLs offers a tremendous opportunity for making hybrid materials by simple mixing. The chance to study the fundamentally important electron transfer, energy transfer, charge transfer interactions, triplet-state emissions, and even detailed NMR experiments in the solvent-free neat state is the major attraction of SOLs. Usually, solvents and their polarity control such molecular properties, and in the case of SOLs, it avoids the use of solvents to study such fundamentally important properties. Besides, SOLs protect the triplet emitters and excited state processes involving triplet states from quenchers and make the analysis possible under ambient conditions. Our effort in this direction was focused on tuning the ground and excited state properties by transforming conventional organic molecules to SOLs and further value addition by preparing the hybrid SOLs. We developed a series of hybrid SOLs, exploring room-temperature phosphorescence, thermally activated delayed fluorescence, charge or energy transfer between donor and acceptor SOLs, selective explosive sensing, etc. A slight variation in the chemical structure or optoelectronic properties of the individual components imparted exciting optical features for the hybrid SOLs. It includes nonemissive charge transfer, tunable emission exciplex, room temperature phosphorescence, and thermally activated delayed fluorescence SOLs. The liquid matrix of donor SOLs accommodated varying amounts of acceptor SOLs to tune the ground and excited state features. In all examples of donor-acceptor-based hybrid SOLs, even a low amount of acceptor, such as a donor-acceptor ratio of 1000:1, can cause pronounced optical properties. Hence, the evaluation of the optical properties of SOLs, especially, in the absence of solvents is so special that it avoids the interference of solvent molecules. Still, the major drawback of SOLs remains unsolved until we report polymerizable SOLs. Although a large variety of SOLs have been reported in the literature, the long-lasting problem of surface stickiness of SOLs was resolved by polymerizable SOLs. It enabled the development of flexible, foldable, and stretchable large-area luminescent films suitable for lighting and display devices. In this Account, we summarize our work on SOLs, hybrid SOLs, polymerizable SOLs, and the application of SOLs in selective sensing of explosives. Finally, an outlook on the feasibility of luminescent polymerizable SOLs in futuristic applications is provided.